REPRESENTATION OF MODERATE ISLAM IN LITERARY TEXTS BY GUS MUS AND THEIR RELEVANCE AS TEACHING MATERIALS IN HIGH SCHOOLS - Shidiq Ardianta; Erisy Syawiril Ammah; Lidia Maziyyatun Nikmah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study examines the representation of moderate Islam in literary texts written by Gus Mus and its relevance as teaching materials in senior high schools. The research aims to identify forms of moderate Islamic values and analyze their suitability for literature learning at the secondary education level. This study employs a qualitative descriptive method using text analysis of selected literary works by Gus Mus and document analysis of the senior high school curriculum. The findings indicate that Gus Mus’s literary texts represent moderate Islam through values of tolerance, humanism, balance, and inclusivity. These values are relevant to support character education and strengthen religious moderation in senior high school learning contexts.